1994
DOI: 10.1063/1.870927
|View full text |Cite
|
Sign up to set email alerts
|

Formation of vortex chains in a nonuniform magnetized electron plasma

Abstract: It is shown that the equations governing the dynamics of weakly interacting medium-frequency electrostatic waves in a nonuniform magnetoplasma with a fixed ion background can have localized vortex chain solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…4 The dynamics of electron plasma vortices in background vorticity distribution has been investigated both analytically and numerically 4 as well as experimentally. 7,9,10 Vortex structures have been observed [11][12][13] in low-temperature laboratory devices in which electron clouds are confined by dc electric and magnetic fields. 7 Possible stationary solutions of the latter can be cast in the form of a global vortex pattern 7,8 and a double vortex.…”
Section: Introductionmentioning
confidence: 99%
“…4 The dynamics of electron plasma vortices in background vorticity distribution has been investigated both analytically and numerically 4 as well as experimentally. 7,9,10 Vortex structures have been observed [11][12][13] in low-temperature laboratory devices in which electron clouds are confined by dc electric and magnetic fields. 7 Possible stationary solutions of the latter can be cast in the form of a global vortex pattern 7,8 and a double vortex.…”
Section: Introductionmentioning
confidence: 99%
“…͑8͒ can be reduced to the ‫ץ‬ z =0 limit of a previously reported set of equations. 18 By using Eqs. ͑1͒ and ͑2͒, and assuming B 0 = const, the governing equation ͑8͒ is reduced to…”
Section: Basic Equationmentioning
confidence: 99%
“…23 It has been shown that the governing nonlinear equations admit stationary solutions in the form of double [19][20][21][22]24 and global vortices 22 and a vortex chain. 18 In the present paper, the formation of vortical structures in a weakly non-neutral electron-ion magnetoplasma is investigated in the medium-frequency regime pi , ci Ӷ Ӷ c , where pi is the ion plasma frequency and ci ͑ c ͒ is the ion ͑electron͒ gyrofrequency. The plasma is non-neutral due to the presence of an unshielded electron population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a great deal of interest [1][2][3] in understanding the linear and nonlinear properties of finite amplitude low-frequency Alfvén-like waves in lowtemperature space and laboratory plasmas. The linear theory [4][5][6] focuses on the derivation of the dispersion relation and identifying the unstable wave spectra, whereas the nonlinear analyses [1][2][3][6][7][8] compute the saturation level of fluctuations as well as develop mode coupling equations which are needed for predicting the salient features of fully developed electromagnetic turbulence in nonuniform magnetized plasmas.…”
Section: Introductionmentioning
confidence: 99%